Impact-induced changes in source depth and volume of magmatism on Mercury and their observational signatures - Sebastiano Padovan (Nature Portfolio, 2017)
Mantle partial melting produced the volcanic crust of Mercury. Here, the authors numerically model the formation of post-impact melt sheets and find that mantle convection was weak at around 3.7–3.8 Ga and that the melt sheets of Caloris and Rembrandt may contain partial melting of pristine mantle material.